THE PIVOTAL ROLE OF PERFORMANCE MANAGEMENT SYSTEMS IN MEDIATING ORGANIZATIONAL AGILITY AND PERFORMANCE - Kwistianus, Hendri; Iskandar, Vido; Wibowo, Yoel; Devie, Devie (Jurnal Akuntansi Kontemporer, 2024)
Research Purposes. This study aims to investigate the influence of organizational agility on organizational performance in the hospitality industry.Research Methods The data analysis technique used is Structural Equation Modeling (SEM) with SmartPLS 4 Software to analyze the relationship between variables. The sampling technique used is non-probability on 105 employees/business owners in the hotel sector with 3-5 stars in Indonesia.Research Results and Findings. The findings show that organization agility does not possess any direct correlation with organization performance among starred hotels in Indonesia. Furthermore, positive and significant correlation from organizational agility to performance can be established through the mediatory of performance management system implementation and supportive organizational culture among the industry. The result of this study generates enticing implications towards hospitality business leaders.